Reliability of hypertrophy of the contralateral testis in prediction of the status of impalpable testis. Issue 3 (July 2017) - Shalaby, Rafik; Alshamy, Ahmad; Abd-Alrazek, Mohamad; Gouda, Samir; Mahfouz, Mohamad; Shahin, Mohamad; Moussa, Sabri; Elhady, Sayed; Algallad, Hassan
Abstract : Background: The hypertrophied testis can predict the status of the impalpable contralateral one. The aim of this study was to assess the accuracy of contralateral testicular hypertrophy for predicting the presence or absence of impalpable undescended testis (UDT) in Egyptian boys. Patients and methods: This study was carried out on 204 patients with unilateral impalpable UDT who presented to the Pediatric Surgery Department, Al-Azhar University Hospitals, from July 2014 to April 2016. Only 40 patients with unilateral impalpable UDT and hypertrophy of the contralateral testes were included in this study. They were subjected to routine laboratory investigations, ultrasonography measurement of the volume of the hypertrophied testis, and diagnostic laparoscopy for the impalpable intra-abdominal testis (IAT). Both ultrasonography and laparoscopic findings were reported. Results: Out of 204 patients with unilateral impalpable UDT, only 40 patients fulfilled the inclusion criteria. Their ages ranged from 1 to 5 years, with a mean of 2.3±1.18 years. Testicular volume ranged from 0.94 to 6.33 cm 3, with a mean of 3.12±1.41 cm 3 . Diagnostic laparoscopy indicated 30 patients with vanishing testis, four patients with low IAT, and three patients with high IAT and three patients with testicular vessels and vas passing internal inguinal ring, where inguinal exploration indicated atrophic testes. Conclusion: Hypertrophied testis can predict the absence of other contralateral impalpable testis when its volume is 1.85 cm 3 .